2009
DOI: 10.1097/mao.0b013e3181b07d41
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Auditory Brainstem Implantation in Prelingually Deaf Children With Inner Ear Malformations Including Severe Stenosis of the Cochlear Aperture and Aplasia of the Cochlear Nerve

Abstract: Our preliminary results show that there is adequate contribution of brainstem implants in the development of auditory-verbal skills. Additional handicaps slow the progress of the prelingually deaf children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 9 publications
(5 reference statements)
3
53
0
3
Order By: Relevance
“…12,34,35 For these patients, ABI is now being investigated as a treatment option. 36 Experience with ABI for CND is limited, and to date, to our knowledge, no studies have examined the influence of concomitant structural brain abnormalities on implant outcomes. We posit that the presence of brain stem malformations may predict poorer ABI outcomes, particularly if the abnormality involves the circuitry of the auditory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…12,34,35 For these patients, ABI is now being investigated as a treatment option. 36 Experience with ABI for CND is limited, and to date, to our knowledge, no studies have examined the influence of concomitant structural brain abnormalities on implant outcomes. We posit that the presence of brain stem malformations may predict poorer ABI outcomes, particularly if the abnormality involves the circuitry of the auditory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It is impossible to estimate the average age of the patients in the studies, since most of them showed results involving patients older than 18 years old. Twelve (10.0%) of the patients had associated anatomic deformities, and 15 (12.5%) had other associated deficiencies or disabilities, as presented in Tables 1 and 2 [7,[10][11][12][13] . Among the studies, 13 patients [10,14] were fitted with the Pulsar CI100 ABI ® (Med-El Co., Innsbruck, Austria), 5 patients were fitted with a Concerto ABI ® (Med-El Co., Innsbruck, Austria) [10] , 1 patient received a Nucleus 22 Auditory Brainstem Implant System ® (Cochlear Co., Lane Cove, Australia) [15] , and the other 48 [7,13,14,[16][17][18][19] were fitted with the Nucleus 24 Auditory Brainstem Implant System ® (Cochlear Co., Lane Cove, Australia).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Most of the studies considered the indication of ABIs for patients with bilateral severe sensorineural hearing loss caused by issues in the cochlear nerve (aplasia or avulsion after a head trauma with bilateral temporal bone fracture, tumors, like sporadic schwannoma of the cochlear nerve, or bilateral tumors caused by neurofibromatosis type 2 [NF2]) [1,[3][4][5][6][7]8] , severe abnormalities of the cochlea (malformations or ossification) [9] , or auditory neuropathy. [1] It is impossible to estimate the average age of the patients in the studies, since most of them showed results involving patients older than 18 years old.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The auditory brainstem implant (ABI), again a modified cochlear implant with a flat array consisting of 12 (ABI by MedEl) to 21 (ABI by Cochlear Ltd.) platinum electrodes on a Dacron mesh backing, was created for NF2 patients [84]. To date, however, ABIs have proven most beneficial for adults without NF2 and in children with cochlear malformations [22,28,140]. In one study involving 48 non-NF2 (nontumor) patients, a mean score of 59% was achieved on openset speech perception tests [27].…”
Section: Auditory Nucleus and Ganglion Stimulationmentioning
confidence: 99%